Salicylates used in inflammatory bowel disease and colchicine impair interferon-gamma induced HLA-DR expression. Issue 1 (January 1992) - Crotty, B; Hoang, P; Dalton, H R; Jewell, D P
Abstract : Colonic epithelial cells express HLA-DR in inflammatory bowel disease. The effect of drugs used in the treatment of inflammatory bowel disease and colchicine on interferon-gamma (IFN-gamma) induced DR expression has been investigated. HT-29 cells were cultured in 25 cm2 flasks. At 48 hours interferon-gamma (0, 50, or 100 U/ml) +/- drug were added. At 120 hours the cells were stained for HLA-DR and analysed by flow cytometry. 10(-2) M 5ASA reduced DR expression induced by 50 U/ml interferon-gamma from 62 (12)% of cells (mean SD) to 29 (20)% (p less than 0.005). Corresponding figures for 10(-2) M N-acetyl 5ASA were 68 (16)% to 39 (17)% (p less than 0.05); for 10(-2) M 4ASA, 61 (4)% to 57 (4)% (p = 0.6); for 10(-2) M N-acetyl 4ASA, 60 (12)% to 35 (13)% (p less than 0.05); for 10(-2) M olsalazine, 72 (9)% to 3 (1)% (p less than 0.001); for 10(-3) M olsalazine, 72 (9)% to 16 (10)% (p less than 0.001); for 10(-6) M colchicine, 62 (13)% to 5 (3)% (p less than 0.001); and for 10(-7) M colchicine, 62 (13)% to 10 (3)%. Similar results were obtained when DR was induced by 100 U/ml of interferon-gamma except with 10(-2) M 4ASA which reduced expression from 77 (4)% to 68 (3)% (p less than 0.05). Sulphapyridine, prednisolone, indomethacin and cyclosporin A had no effect. Concurrent staining with propidium iodide showed that these results were unchanged when viable cells alone were analysed. Prior incubation of cells with drug, followed by washing, had no effect on interferon-gamma induced DR expression. 5ASA, N-acetyl 5ASA, 4ASA, N-acetyl 4ASA, olsalazine and colchicine reduce interferon-gamma induced HLA-DR expression. In inflammatory bowel disease these compounds may impair antigen presentation by the colonic epithelium.